Magnetic resonance imaging of suspected idiopathic bilateral C2 hypertrophic ganglioneuritis in dogs. (20th January 2015) - Joslyn, S.; Driver, C.; McConnell, F.; Penderis, J.; Wessmann, A.
<x xml:space="preserve">Abstract</x> OBJECTIVES To report the magnetic resonance imaging and clinical features of suspected idiopathic bilaterally symmetric hypertrophic ganglioneuritis affecting the C2 nerve roots. METHODS Retrospective analysis of case records of dogs with imaging findings suggestive of idiopathic bilateral C2 neuritis. Data analysed included signalment, history, clinical signs, clinical pathology results and magnetic resonance imaging findings. Nerve root enlargement and spinal cord changes were classified as clinically significant or incidental, and further graded as mild, moderate or severe based on the degree of spinal cord distortion/compression. Imaging features were also correlated with severity of neurological deficits. RESULTS Twelve dogs, including nine Staffordshire bull terriers showed magnetic resonance imaging features suggestive of idiopathic hypertrophic neuritis of C2 nerve roots. Findings were considered incidental (4/12) or clinically significant (8/12) based on prior neurological examination. Changes were best visualised on transverse images at the level of the C1‐2 intervertebral foramina. The degree of associated spinal cord compression subjectively correlated with the severity of the neurological deficits. All cases with clinically significant lesions that were treated with corticosteroids responded favourably. CLINICAL SIGNIFICANCE Bilaterally symmetric C2 neuritis likely represents idiopathic hypertrophic ganglioneuritis. Staffordshire bull terriers appear over represented. Immunosuppressive doses of corticosteroids should be considered for clinically significant lesions.